Preventive effect of precautionary lowered exposure or adaptation of nanomaterial workers? - Pelclová, Daniela; Navrátil, Tomáš; Schwarz, Jaroslav; Ždímal, Vladimír; Dvořáčková, Štěpánka; Klusáčková, Pavlína; Vlčková, Štěpánka; Rössnerová, Andrea (Central European journal of public health, 2025)
OBJECTIVES: Nanotechnology is a fast-growing field in both science and industry. However, experimental studies brought warning data concerning the negative effect of engineered nanoparticle exposure leading to oxidative stress, inflammation, decreased immune cell viability, and genotoxicity. The consequences of human exposure may appear with decades of latency. Therefore, more data is needed to identify the hazardous effects of nanoparticles. Exposure should be under control and biomarkers of effect are urgently searched. METHODS: Exposures of researchers working with nanocomposites were measured in yearly intervals for 5 years and biomarkers of oxidative stress and/or antioxidant capacity were analysed. Exposure to aerosols with nanoparticles was measured repeatedly using online and offline instruments during both the machining of geopolymer samples with epoxide resin and nanoSiO2 filler and metal surface welding. The levels of biomarkers of oxidation of lipids, nucleic acids and proteins were analysed in exhaled breath condensate (EBC) of researchers and controls in 2016-2018. In 2019 and 2020, glutathione was measured in plasma to assess their antioxidant status. The trends in both exposure and EBC biomarkers' levels were analysed. RESULTS: On average, 21 researchers were examined yearly (aged 40 ± 5 years, exposure 14 ± 3 years). After 5 years, the mean mass concentration dropped from 0.921 to 0.563 mg/m3 and mean total number of particle concentrations from 146,106 to 17,621/cm3. The majority of biomarkers of oxidation of lipids, proteins and nucleic acids decreased (p < 0.05) during repeated measurements from the highest levels being mostly found in 2016. Glutathione in plasma in 2019-2020 was elevated (p < 0.01) as compared to controls. CONCLUSIONS: The adaptation of long-term exposed researchers may give a plausible explanation. However, to our meaning, the precautionary principle and higher attention of the employers to the potential risk of nanoparticles by reducing nanoparticles exposure by almost one order of magnitude played the key role.
Keywords: Nanoparticles; engineered nanoparticles; nanostruktury; Oxidative Stress; adaptation; Adult; Nanostructures; prevention; oxidative stress; Occupational Exposure; Humans; biologické markery; pracovní expozice; nanočástice; spirometry; dospělí; oxidační stres; Biomarkers; lidé